Serum Nerve Growth Factor in the Occurrence of Peripheral Neuropathy in Rheumatoid Arthritis Patients - Rudy Hidayat; Ridho Adriansyah; Ahmad Yanuar Safri; Sukamto Koesnoe (Indonesian Rheumatology Association, 2020)
Abstract Background Peripheral neuropathy (PN) is an extraarticular manifestation in rheumatoid arthritis (RA). In type-2 diabetes mellitus (DM) patients, Nerve Growth Factor (NGF) is associated with PN. The correlation between NGF level and PN among RA has not been concluded yet. This study aimed to determine the mean levels of NGF blood serum and its relationship to PN among RA patients. Method A cross sectional study using consecutive sampling method including patient of rheumatology clinic Cipto Mangunkusumo Hospital was performed between July 2015 to March 2016. The NGF level measurement and Electromyography-Nerve Conduction Velocities (EMG-NCV) were examined to the subjects. Patients were classified into 2 groups; PN positive and PN negative. Bivariate analysis was done to investigate the relationship between NGF and PN among groups. Secondary data such as age, sex, Erythrocyte Sedimentation Rate (ESR), CRP, Disease Activity Score (DAS)28-ESR and CRP are obtained from medical record. Result Among 132 subjects, PN was found in 60 subjects. The median of NGF level in RA patients was 4.11 pg/mL (0.0-24.5). The median of NGF level of RA patients with PN was 4.11 pg/mL (1.1-20.83) and without PN was 3.89 pg/mL (0.0-24.5). Types of neuropathy among patients were polyneuropathy (21.97%), mononeuropathy multiplex (15.15%) and Carpal Tunnel Syndrome (11.36%). In this study we found no association between NGF serum level and PN among RA patients (p = 0.716). Conclusion The median of serum NGF level among PN group was higher than without PN. There was no relationship between serum NGF level and PN among patients with RA. Keywords :rheumatoid arthritis, peripheral neuropathy, nerve growth factor